Antibiotic Allergies – Is De-labeling Based on Clinical History Feasible?. (4th October 2017) - Torda, Adrienne; Chan, Victor
Abstract: Background: Up to 25% of patients admitted to hospital have an antibiotic allergy label (AAL), most of which are towards penicillin. However, up to 90% of patients who claim to be allergic to penicillin are actually able to tolerate them 1 . Whilst skin testing is safe and efficacious in de-labeling patients with a penicillin allergy label, it is usually not widely available. Therefore, we investigated the feasibility of de-labeling based solely upon clinical grounds. Quality of allergy documentation and subsequent antibiotic use was also assessed. Methods: This was a cross-sectional study assessing all patients admitted to a tertiary referral teaching hospital over a 5-month period in 2016. All newly admitted patients were prospectively screened for the presence of an antibiotic allergy documented in their electronic medical record. Unless unable to participate, patients were interviewed regarding the detailed nature of their antibiotic allergy. Information regarding allergy documentation, medical condition and antibiotic use was obtained from medical records. Results: 3855 patients were screened, 553 (14.35%) had an AAL, and 352 were interviewed. There were 426 allergies, 276 (64.8%) towards a penicillin. Only 52% of patients had a convincing history consistent with antibiotic allergy, and 48% of these were mild cutaneous reactions. It was felt that de-labeling and direct re-challenge would be relatively safe in 70% (298/42) of AALs (if the mild cutaneous allergic group were included). In patients who were prescribed antibiotics during study admission, 25.6% (41/160) of antibiotic prescriptions in our cohort were found to be inappropriate in patients with AALs. Conclusion: Direct re-challenge based upon clinical grounds appears to be a feasible clinical option in many patients with AALs and would allow de-labeling of these patients. The major barriers continue to be patient acceptance and risk of severe adverse reactions. Our study also found that major improvements could be made in the specific documentation of allergy and also in selection of guideline-recommended alternate antibiotics. 1. Joint Task Force on Practice Parameters. Drug Allergy: An Updated Practice Parameter. Ann Allergy Asthma Immunol. 2010; 105(4): p. 259–273. Disclosures: All authors: No reported disclosures.